Magnesium of Dead Sea Salts as a Key Factor for the Treatment of Seborrheic and Atopic Dermatitis: A Case Report - Sudan, Bernard J.L. (HM Publisher, 2024)
Background: Seborrheic and atopic dermatitis are common and chronic inflammatory skin diseases. Conventional treatments are often ineffective and can have significant side effects. Magnesium dead sea salt has a high concentration of magnesium, and previous research shows its potential to help improve skin conditions. Case presentation: Patients with chronic seborrheic and atopic dermatitis were treated with topical 5% dead sea salt magnesium for 4 days. Patients experienced significant improvement in their symptoms. Conclusion. Dead Sea salt magnesium can be a safe and effective treatment for seborrheic and atopic dermatitis.